(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The rapid expansion of the gig economy has radically reshaped the actual nature of work, undermining the actual accepted concept of the employment a well as labor rights and social protection. The forms of labor code which the digital platforms propose are temp but more recently they are prone to face being outside the vires of labor issues traditional that exposes them to lack reliable income, yet it has its privileges and incompetence of law over the laborers. The country of India has a tremendous growth of gig economy, whereby millions of employees depend upon the applications that cover Uber, Swiggy, or Zomato to get their income. However, this type of workers is normally subjected to significant degrees of oppression like; the absence of being able to accrue socially, the employment system and minimum wages. The current paper is a critical discussion of the compatibility of the social contract with respect to the gig working, and the reminders in the policies on labour laws and social protections systems that should be sought to address the interests and well-being of the gig workers. The analysis relying on the comparative analysis of the global policy practice(s) under scrutiny, the paper will reveal the gap in the existing paradigms (particularly, in the context of India where in relation to the employment of digital gigs, the legislation on labour does not deliver any significant results regarding the specificities of the recently emerged sphere). In the article, the suggestion approaches permitting digital labour market with social security, minimum requirements and labour protection. In the analysis of the labor rights under digitalization era, the paper argues that the more stable and expansive social contract can be received to cash in on well-being, innovativeness, and make-ability of the personnel in the digitalized age, in the so-called emerging economies in the era of digitalization, and India is one of such countries.